Insights into the Origins of Minority Carrier Traps in Solution‐Processed Organic Semiconductors and Their Effects on Transistor Photostability. (7th July 2022) - Ruan, Xiaobin; Cheng, Shuiling; Deng, Wei; Tan, Yuan; Lu, Zhengjun; Shi, Jialin; Zhang, Xiujuan; Jie, Jiansheng
Abstract: Minority carrier traps in the bandgap of organic semiconductors (OSCs) are pervasive and of vital importance in determining the performance and stability of the optoelectronic device. Understanding their origins is one critical issue at both the fundamental and applied levels. However, relevant research has rarely been performed due to the lack of an effective strategy for quantitatively assessing the minority carrier traps buried in OSCs. Here, organic field‐effect transistors (OFETs) operated under strong and long‐term light illumination can be used as a model device to assess the amount of minority carrier traps in solution‐processed OSCs, are proposed. Based on the experimental results and theoretical calculations, first identified hydrated impurities (water and oxygen) in the residual organic solvents primarily contribute to formation of minority carrier traps within the OSC bandgap, giving rise to photo‐induced electrical instability of OFETs. To address this problem, a molecular additive strategy is developed to improve the OFET photostability by releasing trapped electrons from the levels of minority carrier traps. This work not only elucidates the significant role of water and oxygen in the residual organic solvents in forming minority carrier traps but also provides guidelines for improving OFET photostability for practical applications. Abstract : Organic field‐effect transistor (OFET) is demonstrated, which could be an effective model device to quantificationally evaluate the minority carrier traps buried in organic semiconductors. With this technqie, water and oxygen impurities are identified in organic solvents which are the important sources of minority carrier traps that lead to the photo‐induced electrical instability. A molecular additive strategy is further developed to improve OFET photostability.